DECISION-MAKING INFORMATION TECHNOLOGY FOR FLEXIBLE INTEGRATED MANUFACTURING - Oleksandr Tsymbal; Artem Bronnikov (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of the study in the article is flexible integrated robotic systems. The aim of the work is to integrate models and decision-making methods in order to create information technology for flexible production. The following tasks are solved in the article: analysis of current trends in the development of production systems, consideration of intellectual decision-making systems as one of the key elements of automated control systems, consideration of the creation of information technology, based on a set of methods and decision models, including adaptive decision making for non-deterministic tasks. Research methods are the theory of sets and the theory of predicates. The following results were obtained: the main problems of the development of flexible integrated systems of modern production were analyzed and formulated. As a new element in the technological systems, it is proposed to introduce the intelligent production agents implemented as mobile robotic platforms capable of performing transport and assembling functions, executing the monitoring tasks, and establishing the basic requirements for them. From the formal point of view, the decision-making process in flexible robotic systems is considered, based on the interaction of the properties of the robotic system, the properties of the working space and the set of possible solutions. The fulfillment of each individual technological task involves the development and implementation of a plan of work of robotic equipment, the set of variants of which is a strategy of functioning of the intellectual robotic system, described in the form of predicate logic. To solve the required technological tasks, the use of the automatic procedures of the generator of solutions, which operates based on the frame-like structures is proposed. The decision-making process consistently supports the consistent decision-making information technology in a robotized production system based on the models of different types. Conclusions: application of the concept of the intellectual agent in the production environment requires the integrated application of models and methods of decision making, which can be a separate information technology of robotic production.